Model and data engineering : Third International Conference, MEDI 2013, Amantea, Italy, September 25-27, 2013. Proceedings - Maabout, Sofian; Cuzzocrea, Alfredo (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the Third International Conference on Model and Data Engineering, MEDI 2013, held in Amantea, Calabria, Italy, in September 2013. The 19 long papers and 3 short papers presented were carefully reviewed and selected from 61 submissions. The papers specifically focus on model engineering and data engineering with special emphasis on most recent and relevant topics in the areas of model-driven engineering, ontology engineering, formal modeling, security, and database modeling.